Terapi Komunikasi Terapeutik Islam untuk Menanggulangi Gangguan Psikologis Anak Korban Bullying - Moch. Khafidz Fuad Raya (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Islamic therapeutic communication aims to assist the patient in the process of healing or restoring his health by giving positive suggestions so that the patient wishes to heal through the principles of Islam. The child of Bullying has a psychological problem that is very dangerous to his mental health, whether it appears symptom or not. This study seeks to explore how Islamic therapeutic communication can provide preventive, curative, and rehabilitative (rehabilitation) solutions to solve the psychological problems of bullying children by using therapies that help restore their psychological balance to create communication which is effectively optimal with positive goals through Islamic values.